HUBUNGAN PERSONAL HYGIENE DENGAN PENYAKIT KECACINGAN PADA SISWA SDN 113 KUNGKAI BARU KABUPATEN SELUMA - Sismi, Elsa Prihatin (JURNAL MEDIA KESEHATAN, 2015)
Worm infection disease is a disease that is often overlooked because it does notdirectly cause death. One reason could be transmitted through soil, called nematoda bowels.Prevalence of worm infection Bengkulu province according to the city health departementBengkulu 2010 was 18 % - 23 % of cases occur in children of primary school age, NewKungkai village there are 41,9 % of children were infected with intestinal worms. Based onthe initial survey dated 7 February 2015, the SDN 113 New Kungkai is one of the schools thatstill have a school yard in the form of soil moist, shaded by trees, poor environmentalsanitation situation maintained that there are many scattered garbage. By mark worms 80 % ofstudents who are anemic as lethargy, pale face, weight loss, listlessness, lack of concentrationstudied, pale eyes, it is because there are many students who have not applied with goodpersonal hygiene, such as not washing hands before eating cafeteria, student habits rarely cutnails, there is still a long nail black and the students still love playing ground with no weargood footwear when out to play and at school. The purpose of this study was to determine therelationship between personal hygiene worm disease in SDN 113 New Kungkai Seluma.Design study used cross sectional. The study sampel was grade 1 to 6, amounting to 27people. Sampling technique used is propotional random sampling. Data were analyzed withunivariate an bivariate (square test with a P value α = 0,05) of 72 respondents in gettingresults 49 (68,1%) of respondents who have poor personal hygiene and 43 (59, 7%)respondents had positive worm. Bivariate analysis results showed that P = 0,001 < α = 0,05values showed no relatoinship between personal hygiene with worming with OR 95 % CI =6,330. Noteworthy health education to the students about the worms and the importance ofhealthy behavior and clean.